Clinical and immunological variants of ANCA-associated systemic vasculitis: a look at the phenomenon of IgG4 overproduction. Literature review and own observations - T. V. Beketova; N. V. Kokosadze (Научно-практическая ревматология)
Systemic vasculitis (SV) associated with anti-neutrophilic cytoplasmic antibodies is a multifactorial process characterized by the variability of the epitope specificity of anti-neutrophilic cytoplasmic antibodies and the diversity of clinical phenotypes of the disease. In recent years, there has been an increasing interest in the combination of AAV and the phenomenon of IgG4 hyperproduction, which varies widely within AAV, from anti-neutrophilic cytoplasmic antibodies products of IgG4 subclass of undetermined significance, the presence of IgG4 positive plasma cells in the foci of immunoinflammatory lesions in patients with a definite diagnosis of AAV, to the typical clinical manifestations of an IgG4-related disease (IgG4-RD). We introduce own clinical case and analyze the combined data of the literature, which included 35 cases of a combination of AAV and IgG4-related pathology, indicating existing differences in the clinical manifestations of classical IgG4-RD and when combined with AAV. The currently accumulated data allows us to discuss the allocation of a specific clinical and immunological variant of AAV with IgG4 hyperproduction, characterized by a combination of clinical manifestations of AAV and clinical and / or histological signs of IgG4-related pathology. It is important to emphasize that the allocation of phenotypes of AAV in the future may be important for the personalized choice of treatment tactics for patients.